2022
DOI: 10.1097/scs.0000000000008627
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Financial Analysis of Craniosynostosis Surgery in the United States

Abstract: Background: The purpose of this study was to investigate the financial implications of demographic and socioeconomic factors upon the cost of surgical procedures for craniosynostosis. Methods: A retrospective cohort study was conducted of admissions for craniosynostosis surgery in the United States from 2015 through 2020 using the Pediatric Health Information System. Patient demographics, case volume, and surgical approach were analyzed in context of hospital charges. Results: During the study interval, 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Access to craniosynostosis evaluation and surgical care varied based on patient race, insurance status, and socioeconomic status (Table 1). Seventeen of the 28 studies analyzed differences in time to craniosynostosis diagnosis, referral, or surgical intervention (7 single-institution cohort reviews, 10 national database reviews, and 2 dual-institution cohort revi ews) 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Ten 3,4,[7][8][9]11,13,15,17,19 of the 17 studies investigated racial disparities in access to care, all of which found that non-white patients were more likely to experience a delay to at least one step of the diagnostic process (i.e., diagnosis, referral, or intervention) compared to White patients.…”
Section: Time To Diagnosis Referral and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to craniosynostosis evaluation and surgical care varied based on patient race, insurance status, and socioeconomic status (Table 1). Seventeen of the 28 studies analyzed differences in time to craniosynostosis diagnosis, referral, or surgical intervention (7 single-institution cohort reviews, 10 national database reviews, and 2 dual-institution cohort revi ews) 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Ten 3,4,[7][8][9]11,13,15,17,19 of the 17 studies investigated racial disparities in access to care, all of which found that non-white patients were more likely to experience a delay to at least one step of the diagnostic process (i.e., diagnosis, referral, or intervention) compared to White patients.…”
Section: Time To Diagnosis Referral and Interventionmentioning
confidence: 99%
“…3,15 Six studies investigated the consequences of presenting for surgery at an older age. 6,10,14,16,18,20 Of these, one national database review found that older age at the time of surgical intervention was associated with increased surgical complication rate and increased hospital length of stay. 10 Five studies (3 national database reviews and 2 single-institution cohort reviews) found that older patients were more likely to undergo open surgical approaches than those who presented at younger ages.…”
Section: Time To Diagnosis Referral and Interventionmentioning
confidence: 99%
“…Recent work discussing craniosynostosis care suggests higher-volume centers (80th percentile or above) yield superior patient outcomes including significantly lower hospital admission charges, shorter intensive care unit (ICU) length of stay, and lower ICU charges. 8 High-volume craniosynostosis surgery centers also performed endoscopic procedures twice as often as open procedures. 8 Although the election for endoscopic versus open procedures is certainly a multifaceted one, emerging literature highlights the favorable peri- and postoperative profile of endoscopic approaches for several craniofacial operations, including reduced blood loss, 13 decreased operative time, 13 and shorter ICU length of stay.…”
Section: Centersmentioning
confidence: 99%
“…8 High-volume craniosynostosis surgery centers also performed endoscopic procedures twice as often as open procedures. 8 Although the election for endoscopic versus open procedures is certainly a multifaceted one, emerging literature highlights the favorable peri- and postoperative profile of endoscopic approaches for several craniofacial operations, including reduced blood loss, 13 decreased operative time, 13 and shorter ICU length of stay. 14,15 Additionally, academic institutions often have multiple clinicians in any given specialty from which knowledge bases can be tapped to maximize patient care.…”
Section: Centersmentioning
confidence: 99%
See 1 more Smart Citation